The Effect of Using Environmental Observation Strategy on Students Writing Skills in Descriptive Text - Hofifah, Hofifah; Rosnija, Eni; Rahmani, Eka Fajar (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
The Environmental Observation Strategy is the approach that separating students into groups and having them observe a specific topic for 10-15 minutes before putting to their ideas. Afterward, groups merge their thoughts to create a descriptive paragraph. This research study aims to investigate the significant effectiveness of utilizing the Environmental Observation strategy in enhancing the writing skills of seventh-grade students in the descriptive text at SMPN 10 Pontianak. Employing a pre-experimental research design with a one-group pre-test and post-test approach, the study selected a sample of 32 students through cluster sampling as the sampling technique. Data collection involved administering pre-tests and post-tests in descriptive writing assessments. Statistical analysis comprised t-tests and effect size calculations. The results unequivocally demonstrate the significant impact of the Environmental Observation Strategy on students' descriptive writing skills. The t-test analysis (8.244) surpassed the critical value (2.0395) with df = 31, indicating a strong effect (effect size = 1.428). These findings underscore the pivotal role of implementing the Environmental Observation Strategy to enhance descriptive writing skills, thereby warranting its recommendation for seventh-grade students. By providing students with opportunities to observe and engage with their environment, educators can foster a deeper understanding of descriptive language and encourage students to effectively communicate their observations and experiences through writing.